2016
DOI: 10.1080/0966369x.2015.1136806
|View full text |Cite
|
Sign up to set email alerts
|

Problems and possibilities on the margins: LGBT experiences in the 2011 Queensland floods

Abstract: Vulnerability to disasters is not inherent to particular social groups but results from existing marginality. Marginalisation from social, political and economic resources and recognition underpins vulnerability and impedes recovery. Yet concurrently, disasters can reveal the resilient capacities of some marginal groups, who often develop specific means of coping with marginality. This article applies these perspectives to the experiences of LGBT (lesbian, gay, bisexual, trans) people during the 2011 disaster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 34 publications
0
44
0
3
Order By: Relevance
“…Whilst this paper is conceptual in its focus, elsewhere we are reporting the empirical experiences of LGBTI people in disasters. For example, [35] noted that research participants reported significant concerns in relation to accessing emergency services, shelters and other types of official relief and recovery assistance provided by faith-based Christian institutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst this paper is conceptual in its focus, elsewhere we are reporting the empirical experiences of LGBTI people in disasters. For example, [35] noted that research participants reported significant concerns in relation to accessing emergency services, shelters and other types of official relief and recovery assistance provided by faith-based Christian institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Issues facing sexual and gender minorities; access to emergency shelters; access to support services; gay male privilege in LGBTI communities; relations between LGBTI communities and mainstream emergency services; occlusion in mainstream media and policies [32,33,34,35,36] 2011 earthquake Christchurch, New Zealand…”
Section: Japan Trans and Intersex Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…My interest in exploring memories of the 1974 floods emerged while researching a separate project about the impacts of social marginality on the disaster experiences of lesbian, gay, bisexual, and transgender communities (Dominey‐Howes et al ., ; Gorman‐Murray et al ., ; McKinnon et al ., ). The 2011 floods were one of four case studies for that project, and I conducted a small series of eight semi‐structured interviews in Brisbane in March 2014.…”
Section: Data: Linking Individual Memories Media Reporting and Commmentioning
confidence: 97%
“…This call to 'queer disasters' takes into account the vulnerabilities, needs and resilience of LGBTI populations. LBGTI people: need a voice in disaster management and recovery (Gorman-Murray et al, 2017); have specific shelter and housing needs (Gorman-Murray et al, 2014); and, are vulnerable yet possess an array of capabilities for disaster impact reduction (Gaillard et al, 2017). This important scholarship builds on feminist geographical research that focuses on the intersections of embodied vulnerability and adaptive capacities in natural disaster situations (Hyndman, 2008;Reed and Christie, 2009;Seager, 2006).…”
mentioning
confidence: 99%